Clinical Study of Gracilis Musculocutaneous Flap for Vulvovaginal Reconstruction after Wide Vulvectomy or Total Pelvic Exenteration - Kanazawa, Kouji; Kitashiro, Takeshi; Moriyama, Tomohiro; Ibaraki, Kunio; Futenma, Choujou; Arakaki, Akira; Tazaki, Noriaki; Higashi, Masahiro; Kanaya, Fuminori (Orthopedics & Traumatology, 1994)
The authors report eight cases with skin defects of the genital area following radical or wide resection of gynecologic malignant tumors, who have been successfully treated by reconstruction of the vagina and genital skin with bilateral pedicle gracilis musculocutancous flaps. The advantages of this reconstruction are as follows: 1) Gracilis is an expendable muscle and the donor site can be closed primarily. 2) Flap dissection is relatively easy. 3) Satisfactory volume can be transferred by using bilateral gracilis musculocutane-ous flap. 4) Reconstruction of the vagina, the urethral and vaginal orifices are easy by flaps. Two patients complained of gait disturbance and difficulty in urination because of the bulk of this flap. The authors would like to emphasize that this reconstructive method, if applicable, is indicated for reconstruction of genital tissue defects and urethral and vaginal orifices.